Exploiting Cooperative Catalysis for the On‐Surface Synthesis of Linear Heteroaromatic Polymers via Selective C–H Activation. Issue 5 (14th December 2021) - Liu, Xunshan; Matej, Adam; Kratky, Tim; Mendieta‐Moreno, Jesús I.; Günther, Sebastian; Mutombo, Pingo; Decurtins, Silvio; Aschauer, Ulrich; Repp, Jascha; Jelinek, Pavel; Liu, Shi‐Xia; Patera, Laerte L.
Abstract: Regiospecific C−H activation is a promising approach to achieve extended polymers with tailored structures. While a recent on‐surface synthetic approach has enabled regioselective homocoupling of heteroaromatic molecules, only small oligomers have been achieved. Herein, selective C−H activation for dehydrogenative C−C couplings of hexaazatriphenylene by Scholl reaction is reported for the first time. By combining low‐temperature scanning tunneling microscopy (STM) and atomic force microscopy (AFM), we revealed the formation of one‐dimensional polymers with a double‐chain structure. The details of the growth process are rationalized by density functional theory (DFT) calculations, pointing out a cooperative catalytic action of Na and Ag adatoms in steering the C−H selectivity for the polymerization. Abstract : The cooperative catalytic role of sodium and silver adatoms in steering the on‐surface polymerization of hexaazatriphenylene molecules on Ag(111) is demonstrated. By combining high‐resolution scanning probe microscopy with density functional calculations, we elucidate how complex surface processes can be enabled by addition of atomic species designed for catalyzing specific reaction steps.